Activity-Based Costing of Services in Male Surgical Ward, Uttaradit Hospital - Thippinwong , Malaiwan; Akkadechanunt , Thitinut; Chitpakdee , Bunpitcha (Nursing Journal CMU, 2020)
Activity-based costing is the process which assigns costs to health service activities. The objective of this descriptive study was to study the activity-based costing of services in patients with appendicitis, hernia and benign prostate hyperplasia, admitted in the male surgical ward, Uttaradit Hospital and to compare the activity-based cost of services with the budget allocated from the National Health Security Office. The population included service activities for patients with appendicitis, hernia and benign prostate hyperplasia admitted in the male surgical ward, Uttaradit Hospital from 1 July to 30 September 2017. The conceptual framework used for this study was the four steps of the Activity-Based Costing, developed by Kaplan and Cooper in 1998. The instruments used in this study consisted of the service activity dictionary, time spent record form for service activities, the data record forms for labor costs, material costs, and capital cost. All instruments were validated for content by three experts and the inter-rater reliability of two data collectors using the same instruments, the same activity and at the same time by starting the timer until the end of each activity. Get the corresponding precision in every activity was 1.0. Data were analyzed by descriptive statistics. The results were: The activity-based cost of services in patients with appendicitis per admission was 3,260.18 Thai baht (THB). The ratio of labor cost : material cost : capital cost was 59.76: 40.02 : 0.22 which was less than the budget allocated from the National Health Security Office at 694.95 THB. The activity-based cost of services in patients with hernia per admission was 1,876.24 THB. The ratio of labor cost : material cost : capital cost was 70.89 : 28.81 : 0.30 which was less than the budget allocated from the National Health Security Office at 2,078.89 THB. The activity-based cost of services in patients with benign prostate hyperplasia per admission was 6,152.89 THB. The ratio of labor cost : material cost : capital cost was 45.57 : 54.30 : 0.13 which was higher than the budget allocated from the National Health Security Office at 2,584.90 THB. The results of this study will provide base line data for hospital and nurse administrators to manage resources used in service activities for patients with appendicitis, hernia and benign prostate hyperplasia. Additionally, the process of costing will be the model to analyze activity based cost of other services in Uttaradit Hospital.